TEACHER AND STUDENTS' CODE SWITCHING IN EFL CLASSROOM: A Case Study at a Junior High School in Bandung - Rahman, Arif (2009)
This study investigates a phenomenon of social interaction in which the use of one language is switched to another language, known as code switching (CS). More specifically, the study focuses on the types of CS and the functions of CS in EFL classrooms at a Junior High School in Bandung. The phenomenon was investigated using qualitative research design, embracing the characteristics of a case study. The data were obtained from classroom observations through audio recording and field notes. The finding reveals that both the teachers and the students employed three types of CS: inter-sentential, tag-switching, and inter-sentential switching. It is found that inter-sentential switching occurred more frequently in Regular class than in RSBI class. The finding also shows that the different frequency of CS function occurs both in two classes seems to demonstrate that the speakers in the two classes have different ability in using the target language (in this case, English). This gives support to the study of Ene (2007; see also Gregio & Gil, 2006) which reports that the amount of CS would be more highly in the speech of less fluent bilinguals. This study seems to suggest that the participants in Regular class are less fluent in English than those in RSBI class since the number of CS functions in student function is much bigger in Regular class than that in RSBI class. The data further shows that the teachers and the students switched code during the lesson for two reasons: for social and pedagogical functions. Socially, CS in this study served as (1) conveying teacher's admonition, (2) requesting for help, (3) helping other students, (4) commenting on the students' unsatisfactory answers, and (5) building unofficial interaction among the students. Pedagogically, CS served to (1) explain or repeat ununderstandable utterances which has been said previously in order to help students understand it, (2) check the students' understanding to the new words or expression introduced in the lesson, (3) translate sentence when students learn about grammatical features (4) repair self mistakes, (5) clarify teachers' misunderstanding, and (6) initiate a question. The finding shows that English is usually used in materials-dependent talk. Meanwhile, Indonesian is reserved for students to students' interaction, disciplinary talk or students' initiation. This is in line with finding of Canagarajah (2001) who says that English is used as material-base communication, while L1 is used for other activity (e.g. serve as functions of code switching).